Wives’ multiple roles in supporting coastal families’ economy - Hapsari Ayu Kusumawardhani; Indah Susilowati (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2021)
This study aims to explore the triple role of fishermen's wives, analyze how they contribute to their families' economy, and determine appropriate strategies for fishermen's wives to support household economies in the coastal area of Tegal City. This study finds that, on average, fishermen's wives have low educational levels and limited economic access. We use the mixed method (combining the quantitative and qualitative approaches) to analyze the data from 100 respondents selected with the purposive sampling method. Additionally, we also conduct in-depth interviews with selected key persons. Our results indicate that fishermen's wives in Tegalsari and Muarareja villages have triple roles (production, reproduction, and community management). They work to earn revenues while playing their domestic role (becoming housewives) and play active roles in their social lives. Further, these wives contribute significantly to their families' incomes. We then use ATLAS.ti as a qualitative analysis tool to analyze strategies for empowering fishermen's wives from the economic, cultural, and institutional aspects.